2014
DOI: 10.1128/aac.03106-14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Third-Generation-Cephalosporin Administration in Hatcheries on Fecal Escherichia coli Antimicrobial Resistance in Broilers and Layers

Abstract: We investigated the impact of the hatchery practice of administering third-generation cephalosporin (3GC) on the selection and persistence of 3GC-resistant Escherichia coli in poultry. We studied 15 3GC-treated (TB) and 15 non-3GC-treated (NTB) broiler flocks and 12 3GC-treated (TL) and 10 non-3GC-treated (NTL) future layer flocks. Fecal samples from each flock were sampled before arrival on the farm (day 0), on day 2, on day 7, and then twice more. E. coli isolates were isolated on MacConkey agar without anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 27 publications
5
50
0
7
Order By: Relevance
“…Despite the high prevalence at day 7, CMY-2-E. coli was not able to persist in the chickens. Other studies in poultry have also shown a decreasing prevalence of antibiotic resistant bacteria, with and without the use of antibiotics (Diarra et al, 2007;Baron et al, 2014;Huijbers et al, 2015). However, most of these studies report limited reduction.…”
Section: Resultsmentioning
confidence: 84%
“…Despite the high prevalence at day 7, CMY-2-E. coli was not able to persist in the chickens. Other studies in poultry have also shown a decreasing prevalence of antibiotic resistant bacteria, with and without the use of antibiotics (Diarra et al, 2007;Baron et al, 2014;Huijbers et al, 2015). However, most of these studies report limited reduction.…”
Section: Resultsmentioning
confidence: 84%
“…Unfortunately, as expected, it has been demonstrated that the use of antimicrobial agents in husbandry is directly related to the incidence of resistant bacteria in FPA (Baron et al . ; Chantziaras et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of ESBL and AmpC‐mediated β‐lactam and cephalosporin resistance among poultry pointed to the use of cephalosporins in hatcheries (administered in ovo or at hatching) as a likely driver for colonization of birds by E. coli (and, in one study, Salmonella ) that were cephalosporin resistant (Dutil et al., ; Persoons et al., ), with one study showing hatchery use to be highly significant in a multivariable regression model for the flock‐level prevalence of cephalosporin resistant E. coli (Baron et al., ). More broadly, recent rapid expansion of ESBL‐type resistance among nonclonal isolates of E. coli from livestock strongly suggests horizontal transmission as the dominant mode of resistance acquisition (Scientific Advisory Group on Antimicrobials of the Committee for Medicinal Products for Veterinary Use, ).…”
Section: Introductionmentioning
confidence: 99%